2015
DOI: 10.1155/2015/895860
|View full text |Cite
|
Sign up to set email alerts
|

Absence of themecA Gene in Methicillin ResistantStaphylococcus aureusIsolated from Different Clinical Specimens in Shendi City, Sudan

Abstract: Absolute dependence on mecA gene as the defining standard in determining the resistance of S. aureus to methicillin became the subject of distrust by many researchers. The present study aimed to determine the frequency of mecA gene in methicillin resistant S. aureus (MRSA) isolates using polymerase chain reaction and to correlate its presence to conventional method. In this regard, two hundred S. aureus isolates were collected from patients with different diseases attending different hospitals in Shandi City, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
48
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 23 publications
14
48
2
1
Order By: Relevance
“…In agreement with our results, the absence of mecA gene within resistant staphylococcal isolates was reported worldwide [38–40]. For example, Elhassan et al reported twelve out of the 123 MRSA isolates (9.8%) were mecA negative when using PCR targeting mecA gene [41]. Inconsistency between phenotypic and genotypic findings may result from mutations in the primers binding sites within the gene.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our results, the absence of mecA gene within resistant staphylococcal isolates was reported worldwide [38–40]. For example, Elhassan et al reported twelve out of the 123 MRSA isolates (9.8%) were mecA negative when using PCR targeting mecA gene [41]. Inconsistency between phenotypic and genotypic findings may result from mutations in the primers binding sites within the gene.…”
Section: Discussionsupporting
confidence: 90%
“…Here, resistance to oxacillin by disk diffusion was detected in 13 of 44 strains (29,55%). However, PCR analysis for mecA revealed that seven out of the 13 strains classified as resistant to oxacillin by disk diffusion harbored the mecA gene and five strains that were positive for mecA (ELHASSAN et al, 2015;BOURGUIGNON et al, 2016). Although, mecA seems to be the most common gene associated with meticillin resistance in S. pseudintermedius, some studies have shown that another gene (mecC) could also be responsible for this resistance profile (KJELLMAN et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, a new mecA homologue mecALGA251 shared 70% nucleotide homology with mecA [41], which results in possible false negative results by using this method. Meanwhile, the detection of the mecA gene is not specific to MRSA, because a small proportion of methicillin-susceptible Staphylococcus aureus (MSSA) with mecA gene and a large proportion of MRSA strains lack of mecA [42,43]. Combination CRISPR-Cas9 with optical DNA mapping was also applied to identify bacterial antibiotic resistance genes [39].…”
Section: Type Ii: Crispr-cas9 Based Diagnosticsmentioning
confidence: 99%